2017
DOI: 10.1037/neu0000408
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychology and cognitive neuroscience in the fMRI era: A recapitulation of localizationist and connectionist views.

Abstract: Objective We highlight the past 25 years of cognitive neuroscience and neuropsychology, focusing on the impact to the field of the introduction in 1992 of functional magnetic resonance imaging (fMRI). Methods We reviewed the past 25 years of literature in cognitive neuroscience and neuropsychology, focusing on the relation and interplay of fMRI studies and studies utilizing the “lesion method” in human participants with focal brain damage. Results Our review highlights the state of localist/connectionist r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…4–6). This is consistent with previous studies highlighting the role of white matter connections in higher-order cognition, such as other decision-making tasks 51,52 , general intelligence 53 , processing speed 42 , and emotional processing 54 . White matter involvement is also highly relevant from a clinical perspective, as one of the most common causes of frontal lobe damage, traumatic brain injury, often involves diffuse axonal injury 55 .…”
Section: Discussionsupporting
confidence: 93%
“…4–6). This is consistent with previous studies highlighting the role of white matter connections in higher-order cognition, such as other decision-making tasks 51,52 , general intelligence 53 , processing speed 42 , and emotional processing 54 . White matter involvement is also highly relevant from a clinical perspective, as one of the most common causes of frontal lobe damage, traumatic brain injury, often involves diffuse axonal injury 55 .…”
Section: Discussionsupporting
confidence: 93%
“…The PD-MCI subtypes were determined based on performance in neuropsychological tests that assess cognitive functions and not directly anatomical regions. The limits of the localist approach in neuropsychology (one function associated with one region) have been largely demonstrated, especially when lesions involve brain regions that are part of functional networks (Sutterer and Tranel, 2017 ; Warren et al, 2017 ). It suggests that cognitive functions involved a multitude of brain regions and that the network-based brain organization has to be considered when cognitive impairment and anatomical location are analyzed together.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation of thalamic lesions associated with behavioral impairment on multiple tasks is that thalamic lesions are associated with distal disruptions ("diaschisis"; Sutterer andTranel, 2017, Von Monakow, 1911) of cortical systems involved in control functions that impact behavior across multiple cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale meta-analyses of functional neuroimaging research, primarily functional magnetic resonance imaging (fMRI) studies, have found that tasks from many different cognitive domains (e.g., executive function, memory, perception) are associated with increased activity in overlapping thalamic subregions (Hwang et al, 2017;Yeo et al, 2015). Functional neuroimaging findings are nevertheless correlational, because increased brain activity in response to a particular behavior is not evidence that this brain region is necessary for the studied behavior (Sutterer and Tranel, 2017). The lesion method, studying patients with focal damage to the thalamus, can provide a stronger test of whether thalamic hubs are necessary for human cognition.…”
Section: Introductionmentioning
confidence: 99%